Oxygen Defects and Surface Chemistry of Reducible Oxides - Pinto, F. M.; Suzuki, V. Y.; Silva, R. C.; La Porta, F. A. (Frontiers in Materials, 2019)
The magic reducible oxides properties likely are mainly due to the presence of oxygen defects and their rich surface chemistry, which provide a rational pathway to the emergent of entirely new properties. Although significant progress has performed in the last years, nevertheless, it can be stated that they are not fully understood at the nanoscale level so far. This review provides a comprehensive perspective on the oxygen defects and surface chemistry of reducible oxides based on two-dimensional materials. Thus, in this perspective, we intend to discuss some of the main challenges and opportunities in this important field of research in materials chemistry and engineering. From a practical standpoint, chemical insights from defect-engineering may provide vital clues for improving synthetic methods and understanding fundamental nanoscale properties, driving innovation in the field of crystalline materials.